Caracterización citogenética del pez neotropical Brycon henni (Pisces: Characidae) (2008)
ABSTARCT: Brycon henni, is a native fish from Western Colombia is important as food and in sport fishing, and could be cultured in waters between 18 and 28°C. A previous cytogenetic study in branchial cells indicated different chromosomal complements. Total blood samples were seeded in 4 ml Ham-F12 culture medium, supplemented with 0.5 ml Bovine Fetal Serum and 0.7 ml Phyitohemaglutinin M (Gibco®) during 96 hr at 28°C; an antimitotic factor (100μl Colcemid® 10%) was added. Cells were incubated in 10 ml KCl hypotonic solution (0.56%) for 24 min at 37°C, fixed in methanol; acetic acid (3: 1) three times, separated by centrifugations, extended drip, and the chromosomes slides were stained with 5% Giemsa (5%). The best metaphases (6 males and 8 females) were photographed. There was a diploid number of 50 chromosomes: Metacentrics (26M), Submetacentrics (16SM) and Subtelocentrics (8ST). The fundamental number is 100 arms. The evolutionary tendency is type B with no supernumerary chromosomes; a first pair of big metacentric chromosomes is characteristic for Brycon, while no chromosomic sexual heteromorfism was detected. Key words: Karyotype, chromosomes, fish, bryconids, lymphocytes.